2023
DOI: 10.1002/ajhb.23974
|View full text |Cite
|
Sign up to set email alerts
|

Facial cues to physical strength are not always associated with facial masculinity: Comparative study of Europeans and Southern Siberians

Abstract: ObjectivesThe aim of our study was to compare morphometric patterns of facial sexual dimorphism with strength‐face relationship in members of two distinct populations of European and Central Asian origin: Russians and Tuvans.MethodsHandgrip strength (HGS) measures and facial photographs were collected from Russian (n = 233) and Tuvan (n = 187) men and women. We digitized 70 landmarks and semilandmarks on full‐face and 54 landmarks and semilandmarks on profile photos. This was done to capture variation in facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…Earlier studies conducted among representatives of European populations, also demonstrated that facial shape perceived as more trustworthy is female-like (Kleisner et al, 2013;Rostovtseva et al, 2023;Stirrat & Perrett, 2010). However, for Europeans such shape often has somewhat lower upper fWHR, and narrower outline of the lower face, which both correspond to more femalespecific facial features in European populations (Ekrami et al, 2021;Fink et al, 2005;Mezentseva et al, 2023;Rostovtseva et al, 2023). In Buryats, trustworthy-looking faces had less prolonged upper face, and thus had higher upper fWHR (although the differences in fWHR between trustworthy-and untrustworthy-looking Buryat faces did not reach statistical significance).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Earlier studies conducted among representatives of European populations, also demonstrated that facial shape perceived as more trustworthy is female-like (Kleisner et al, 2013;Rostovtseva et al, 2023;Stirrat & Perrett, 2010). However, for Europeans such shape often has somewhat lower upper fWHR, and narrower outline of the lower face, which both correspond to more femalespecific facial features in European populations (Ekrami et al, 2021;Fink et al, 2005;Mezentseva et al, 2023;Rostovtseva et al, 2023). In Buryats, trustworthy-looking faces had less prolonged upper face, and thus had higher upper fWHR (although the differences in fWHR between trustworthy-and untrustworthy-looking Buryat faces did not reach statistical significance).…”
Section: Discussionmentioning
confidence: 90%
“…This caused further exclusion of female photographs from the analysis, and the rest of our study focused only on the male part of the Buryat sample, and only on the male-male facial perception. The lack of association between female facial shape and independent biological or behavioral parameters is a very common situation (Mezentseva et al, 2023;Rostovtseva et al, 2021a;. One of the possible reasons for that may be rooted in less general variability in female facial shape compared with male, due to variability in testosterone-mediated facial traits, which is much higher in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While patterns of sexual dimorphism vary among populations, the association between hand grip strength (HGS) and facial shape demonstrates cross-population consistency 25 27 . Notably, the link between facial shape and HGS is relatively stable, unidirectional and independent of facial masculinity.…”
Section: Introductionmentioning
confidence: 99%